Desenvolvimento de metodologia do projeto do reator eletrônico auto-oscilante com entrada universal - Lopes, Juliano de Pelegrini (2010)
This work presents the design and analysis of an electronic system with universal input to supply a fluorescent lamp. The system includes a self-oscillating electronic ballast and an additional circuit which allows keeping the nominal lamp power although a variation of the input voltage. The electronic ballast design comprises some steps: resonant filter design, self-oscillating gate driver design, additional circuit design and stability test. The electronic ballast is represented as a nonlinear control system in order to achieve a feasible design methodology. Moreover, the system must be analyzed considering the describing function method and the extended Nyquist stability criterion. The proposed electronic ballast must maintain the main characteristics of the traditional self-oscillating electronic ballast. Besides that, the additional circuit has a small number of components and it allows the input voltage full range with automatic selection of the switching frequency. The design, simulation and experimental results of the prototype are presented.